Filsafat Pendidikan Rekonstruksi Menurut George Sylvester Count Dan Harold Rugg Dalam Membangun Masyarakat Baru - Saguntung, Rinta L.; Marse, Marse; Delvryance, Agustihana; Labba, Asriyanti (Jurnal Christian Humaniora, 2024)
This article discusses the educational philosophy of reconstruction according to George Sylvester Count and Harold Rugg in building a new society. This research aims to develop good character and behavior in students through the philosophy of reconstructive education according to George Sylvester Count and Harold Rugg in building a new society. The research method used is literature study. The findings show that these two figures have similar views regarding the importance of education in building a just and equitable society. The conclusion of this article is that the philosophy of reconstruction education can be a strong foundation in building a new, better society.